Comparing costs of standard Breast-Conserving Surgery to Oncoplastic Breast-Conserving Surgery and Mastectomy with Immediate two-stage Implant-Based Breast Reconstruction. Issue 8 (August 2022) - Witmer, Tom J.K.; Kouwenberg, Casimir A.E.; Bargon, Claudia A.; de Leeuw, Daniëlle M.; Koiter, Eveline; Siemerink, Ester J.M.; Mureau, Marc A.M.; Rakhorst, Hinne A.
Abstract: Background: Conventional breast-conserving surgery (C-BCS) has equal oncological outcomes and superior cosmetic and patient-reported outcomes compared to mastectomy with immediate two-stage implant-based breast reconstruction (M-IBR). Oncoplastic breast-conserving surgery (OP-BCS) is increasingly being used, as it often has better cosmetic results and it enables larger tumour resection. However, OP-BCS and M-IBR compared to C-BCS lengthens operative time and might lead to more complications and consequently to additional costs. Therefore, this study aimed to compare costs and complication rates of C-BCS, OP-BCS and M-IBR. Methods: This single-centre, retrospective cohort study, calculated costs for all patients who had undergone breast cancer surgery between January 2014 and December 2016. Patient-, tumour- and surgery-related data of C-BCS, OP-BCS and M-IBR patients were retrieved by medical record review. Treatment costs were calculated using hospital financial data. Differences in costs and complications were analysed. Results: A total of 220 patients were included: 74 patients in the C-BCS, 78 in the OP-BCS and 68 in the M-IBR group. From most expensive to least expensive, differences in total costs were found between C-BCS vs. OP-BCS and C-BCS vs. M-IBR (p=<0.01 and p=0.04, respectively). Costs of OP-BCS and M-IBR were comparable. Complication rates were 5.5% for C-BCS, followed by 17% for OP-BCS, and 34% for M-IBR (p<0.01). Conclusion: Considering total treatment costs, OP-BCS was financially non-inferior to M-IBR, whereas complication rates were higher following M-IBR. Therefore, when considering other benefits of OP-BCS, such as higher patient-reported outcomes and similar oncological outcomes, a shift from M-IBR to BCS using oncoplastic techniques seems justified.